SIMULATION MODELLING AND INNOVATIVE APPLICATION OF MULTI-CRITERIA DECISION MAKING RULE FOR MINIMIZING MAKESPAN IN A LARGE SCALE PRESS-SHOP - Thenarasu, Mohanavelu; Rameshkumar, Krishnasamy; Anbuudayasankar, Singallur Palanisamy (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
Sequencing and scheduling of jobs plays an essential role in improving the performance of the job shop production system. In this paper, a detailed study has been made at an auto ancillary unit to prioritize the jobs in a press-shop. The press-shop considered in this study is similar to a typical job-shop environment. The press-shop is consisting of 32 work stations and can process a maximum of 115 job variants according to the monthly demand. The jobs are processed based on their sequence of operation. The main objective of this paper is to develop a realistic simulation model of the shop floor and to evaluate its performance measures using Priority Dispatching Rules (PDR’s) rules. Static PDR’s and Multi-Criteria Decision Making (MCDM) approach are used in this study to evaluate the performance of the press-shop. Simulation model of the press-shop has been developed using Discrete Event Simulation (DES) package ‘ARENA’. The proposed simulation model is integrated with an innovative application of MCDM approach to prioritize the jobs using the ‘Technique for Order of Preference by Similarity to Ideal Solution’ (TOPSIS). Actual demand scenarios of the press-shop has been simulated using the proposed simulation model and the results are compared with the existing practice. The proposed approach is found to be effective and the monthly demand of the customers are satisfied with the reduction in the makespan. The proposed MCDM approach has been implemented in the real-time environment.